Space occupancy in the hallways of old collective housing: a case study of collective housing in Shanghai - Ying Yang; Yinzhe Xu; Kun Liu; Qin Wei (Journal of Asian Architecture and Building Engineering)
The construction of collective housing in the last century has alleviated housing problems in Shanghai. The current situation of these housing units cannot meet the existing living needs of residents, and occupancy exists in hallways, which will affect the traffic function, pose safety risks and cause certain neighborhood conflicts. This study takes old collective housing on Nanchang Road in Shanghai as the research object, and investigates and analyzes the hallways quantitatively from the three dimensions: area, scale and lighting and ventilation. The occupation patterns and behaviors of the hallway were organized, and the causes, extent, and impact of hallway occupation and renovation characteristics are discussed. A comparative analysis of hallway occupancy of collective housing in this area and other urban centers was conducted. The research shows that the current occupation phenomenon is a relatively stable state. It reflects the real needs of residents’ daily lives and alleviates the housing dilemma to a certain extent. In the renewal and daily management of old communities, tolerance and flexibility can be retained for hallway occupancy behavior, which will help to realize the sustainable use of old collective housing and contribute to the preservation of historical urban residencial morphological texture.